1998
DOI: 10.1063/1.476703
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of adsorption of a polyelectrolyte onto charged surfaces

Abstract: Monte Carlo studies of adsorption of a sequenced polyelectrolyte to patterned surfaces By using off-lattice Monte Carlo simulations, the conditions of adsorption of a uniformly charged polyelectrolyte onto oppositely charged planar and spherical surfaces have been investigated. These conditions are functions of the strength of the electrostatic interaction, Debye screening length, chain length, and charge density and curvature of the surface. The adsorption can be tuned by using any one of these parameters. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
130
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 33 publications
15
130
0
Order By: Relevance
“…Because the charge density (τ) of PAA here is at least twice that of pectin and HA, we include AMPS-containing copolymers ("DMF20" or "DMF25") of the same (relatively low) linear charge density as pectin and HA, i.e., average spacing between charges about 12 Å. 49 The intuitive expectation that binding is diminished by polymer chain stiffness, supported by theory 26 and simulations, 27,53,54 is borne out by the results for micelle binding in Figure 7A. The prefactor in eq 6b, now seen as the slope of the Y c vs I a plots (s), increases nearly proportionally to l p o (See Figure 7, inset), although the strong binding and low slope for PAA could be due to either its higher charge density or to charge mobility discussed in the previous section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the charge density (τ) of PAA here is at least twice that of pectin and HA, we include AMPS-containing copolymers ("DMF20" or "DMF25") of the same (relatively low) linear charge density as pectin and HA, i.e., average spacing between charges about 12 Å. 49 The intuitive expectation that binding is diminished by polymer chain stiffness, supported by theory 26 and simulations, 27,53,54 is borne out by the results for micelle binding in Figure 7A. The prefactor in eq 6b, now seen as the slope of the Y c vs I a plots (s), increases nearly proportionally to l p o (See Figure 7, inset), although the strong binding and low slope for PAA could be due to either its higher charge density or to charge mobility discussed in the previous section.…”
Section: Resultsmentioning
confidence: 99%
“…The prefactor in eq 6b, now seen as the slope of the Y c vs I a plots (s), increases nearly proportionally to l p o (See Figure 7, inset), although the strong binding and low slope for PAA could be due to either its higher charge density or to charge mobility discussed in the previous section. Theory 26 indicates that polyelectrolyte adsorption onto spheres is promoted by a reduction in l 1, a chain stiffness parameter that is an expansion factor for the end-to-end chain length in terms of bare Kuhn length. In agreement with this theory, increased binding strength is seen with a decrease in chain stiffness for three polyelectrolytes with similar charge densities: DMF20/25, HA, and pectin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expectation then is that σ c increase with L p . Muthukumar,19,30 for example, proposed the following relationship: σ c ∼ l K R 2 at constant I, charge per polymer repeat unit (q), colloid radius (R), where l K is the bare Kuhn length (twice the bare persistence length) and R 2 is the expansion factor for the polymeric mean-square end-to-end distance. Linse and co-workers 31,32 reported that a greater number of polyelectrolyte segments would reside near a spherical macroion for polyelectrolytes of low L p in the 0-300 mM salt concentration regime.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant efforts and progresses [5][6][7][8][9][10][11], the understanding of charged complexes is still unsatisfactory and lacks behind that of neutral complexes. Certain insight into the complexation process is typically obtained by approximation schemes, e.g., variational calculations [6 -9], which, however, may lead to controversial results [12] and often apply only in limiting situations such as pointlike particles [9] or large colloidal radii [6].…”
mentioning
confidence: 99%